2012
DOI: 10.1016/j.eneco.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of elasticity price of electricity with incomplete information

Abstract: June 2009 *We are grateful to Iberdrola, the Galician Parliament, the Spanish Ministry of Science and Education and ERDF (projects SEJ2005-08783-C04-04 and SEJ2006-12939) and Xunta de Galicia (project INCITE08PXIB300207PR) for funding this piece of research. We also acknowledge the valuable assistance of Natalia Jorgensen and the comments and suggestions by Francisco Laverón and Gonzalo Sáenz-de-Miera. The authors are also thankful to Iberdrola Distribución S.A. and the Spanish Agency of Meteorology (Ministry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 28 publications
5
45
3
3
Order By: Relevance
“…From the simulations, the absolute value of demand elasticity is estimated to be around 0.49. It is found that the demand elasticity of electricity drawn from our model shows similar or higher levels compared to other estimation results from various countries [46][47][48][49].…”
Section: Modelling Direct and Indirect Emissionssupporting
confidence: 51%
“…From the simulations, the absolute value of demand elasticity is estimated to be around 0.49. It is found that the demand elasticity of electricity drawn from our model shows similar or higher levels compared to other estimation results from various countries [46][47][48][49].…”
Section: Modelling Direct and Indirect Emissionssupporting
confidence: 51%
“…for CDD (Reiss and White, 2005;Psiloglou et al, 2009;Labandeira et al, 2011). The same applies for the Spanish Technical System Operator, which uses 15°C as the threshold for HDD and 20°C for CDD.…”
mentioning
confidence: 96%
“…Nevertheless, this electricity consumption may be influenced by other variables. In previous studies, models on electricity demand usually include income or GDP and temperature or similar climate variable as explanatory variables [43,44,46,[48][49][50][51][52][53]. In this study, per capita income is included in the model in order to take into account the effect of the demand for hospitality services performed by residents of each province.…”
Section: Modelmentioning
confidence: 99%